New strategies for O- and C-glycosylation. - Tan, Hong Yee. (2012)
In part A, we have established an efficient iron-catalyzed decarboxylative C-glycosylation of glycals with β-keto acids via decarboxylative Ferrier rearrangement strategy. This approach provides a wide range of β-keto-functionalized 2,3-unsaturated C-glycosides in moderate to good yields. Good α-selectivities are mainly observed with the use of D-galactals along with the bulkier β-keto acids bearing phenyl moieties. In part B, we have developed a highly regio- and stereoselective formation of β-O-arylpseudoglucals via palladium-catalyzed decarboxylative O-glycosylation strategy. This approach essentially relies on palladium’s decarboxylative feature to eliminate the carboxylate group located in C3 position, subsequently liberating phenolic nucleophile to attack onto the electron deficient anomeric position. This reaction system successfully provides a facile and direct entry to exclusive selectivity for β-O- glycosides.